2018
DOI: 10.51723/ccs.v28i01.117
|View full text |Cite
|
Sign up to set email alerts
|

Tecnologias integradas para controle biológico, mecânico e genético de Aedes aegypti

Abstract: Duas tecnologias alternativas para o controle de Aedes aegypti foram avaliadas: a aplicação espacial de larvicida biológico-Bti em potenciais criadouros peridomiciliares, e a liberação de machos estéreis para inviabilização reprodutiva das fêmeas do mosquito. As ações foram realizadas pelos Agentes dos Serviços de Saúde em 15 vilas da Ilha de Fernando de Noronha, e em uma área (900 imóveis) no bairro da Várzea/Recife/Pernambuco. A efetividade dos métodos foi avaliada por indicadores entomológicos, estimados pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…In Pernambuco, Brazil, Regis and collaborators (2013) successfully reduced the mosquito density using IVM [ 26 ]. Other studies have also demonstrated the effectiveness of the integrated use of mosquito control methods [ 34 , 35 , 36 ]. In this study, we evaluated the impact of alternative integrated control actions on the mosquito density to verify whether there was a reduction in continuous mosquito–human contact, in individual residences, in an area with high levels of Ae.…”
Section: Introductionmentioning
confidence: 99%
“…In Pernambuco, Brazil, Regis and collaborators (2013) successfully reduced the mosquito density using IVM [ 26 ]. Other studies have also demonstrated the effectiveness of the integrated use of mosquito control methods [ 34 , 35 , 36 ]. In this study, we evaluated the impact of alternative integrated control actions on the mosquito density to verify whether there was a reduction in continuous mosquito–human contact, in individual residences, in an area with high levels of Ae.…”
Section: Introductionmentioning
confidence: 99%